ANALYSIS OF THE COMMERCIAL MARKET STRATEGY OF PUTRIS FURNITURE IN THE CITY OF KUPANG - Ekaristin Allung; Paulus Un; Nixon Rammang (Wana Lestari, 2020)
UD. Empat Putri is one of the companies engaged in furniture in Kupang City. UD. Empat putri usually get a suppliers of wood raw materials from Atambua, Malacca, Kefa and Soe. The purpose of this research is expected to provide solutions to UD. Empat Putri businessfurniture about an effective and efficien tmarketing strategy therefore the company could maintain and develop the market. In addition, because the main raw material in the furniture industry is wood, therefore it is necessary to have an appropriate marketing strategy therefore the business furniture industry can continue to run, but the forests as the main source of raw material for the furniture industry namely wood, remain the sustainable. This research was conducted for 2 months, starting from March 2019 to April 2019. Data collection was conducted directly from the owner and the owner workforce by using a questionnaire or a list of questions that have been prepared. The results of the interview were analyzed by using the SWOT analysis method. The results showed that UD. Empat Putri has excellent strength for the development of the furniture marketing industry while still prioritizing the legality of the raw material, namely wood. With this legality requirement, it can make it easier for UD. Empat Putri in producing and marketing its products to the market. Based on the results of the SWOT diagram analysis, it can be seen that UD. Empat Putri are in quadrant I, which is UD. Empat Putri has the potensial to develop marketing for furniture products and companies can take the advantage of the existing strengths and opportunities. However, the weaknesses and treats that exist must still be vigilant